Where does subclinical hypothyroidism start? - Zöphel, K.; Wunderlich, G.; Grüning, Th.; Koch, R.; Döge, H.; Kotzerke, J. (Nuklearmedizin - NuclearMedicine, 2005)
The upper limit of the TSH reference range is currently under discussion. In its recent guidelines, the National Academy of Clinical Biochemistry (NACB) recommended the use of ~2.5 mIU/L, rather than ~4 mIU/L, due to the fact that reference populations, on which the definition of the reference range is based, contain persons undergoing an initial phase of autoimmune thyroid disease. This will skew the upper reference limit of TSH. Ultrasonography, in addition to measurement of thyroid autoantibodies, should be used to exclude these persons. Objective: The present study investigates whether the NACB recommendation also applies for a region of mild iodine deficiency. Methods: According to NACB criteria, a reference population (713 persons) was defined out of a total study population of 1442. The TSH reference range was calculated in this reference group and in further subgroups by percentiles. The results were compared with the total study population and the NACB recommendation. All assays used were provided by BRAHMS Diagnostica AG, Hennigsdorf, Germany. Results: As expected, all median TSH values, excluding the median of the group with a hypoechogenic thyroid were close to 1.2 mIU/L. The 97.5th percentile in the reference population was 3.35 mIU/L. However, there was no difference compared to the total study population. Conclusion: The upper reference limit for TSH based on a reference population according to NACB criteria came down to 3.35 mIU/L, but not to ~2.5 mIU/L. Interestingly, there is no difference compared to the total study population.
Keywords: Thyroid stimulating hormone; subclinical hypothyroidism; TSH reference range; thyroid gland